Urban Forestry: environmental perceptions of residents os neighbourhoods Bom Pastor And Centro city Uba/MG - Pizziolo, Bruna Vieira; Tostes, Renata; Silva, Kelly; Arruda, Viviane Modesto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Environmental awareness is responsible for understanding the man of the interrelationships of the individual with the environment . Without a satisfactory level of environmental awareness, individuals tend to hamper implementation of environmental projects , making many of them unviable . This work aims to analyze the environmental perception of residents in Uba regarding urban forestry , with a view to imple- menting an environmental education project in the city . For this we applied a questionnaire to residents of two neighborhoods in the central city. The results show that people recognize the benefits of trees in urban microclimate control , but does not have a proper knowledge about all the benefits of urban forestry , and is responsible for its maintenance . These data reinforce the need for planning afforestation of the municipality with the implementation of an environmental education project , seeking to raise awareness of its importance.